Cryo-preservation of varieties of the genus Phaseolus through viability in Quiroga Parish, Cotacachi Canton1” - López Flores, María Fernanda (2019)
The Quirogaof Cotacachihas a wide range of native varieties of the genus Phaseolus, this is a genus that belongs to the Fabaceae family, they are known as beans, beans or beans, but in recent years the varieties of this genus have suffered a decrease of its genetic variability, due to the anthropogenic impacts thus losing the ancestral knowledge of the place. For this reason, it has been seen the need to conserve the genetics of the varieties of the genus Phaseolus, through cryopreservation to maintain their viability as a function of time. Within the investigation, the study area was identified, establishing five sampling points, where the collection of 23 bean varieties was carried out. Subsequently, the cryopreservation protocol was carried out through the “rapid drying and freezing of seeds” technique, where the samples were subjected to a temperature of -196 ° C in liquid nitrogen, as a comparator the traditional technique of “cold storage” was used, of seeds”, where the samples were subjected to a temperature of -10°C, these two tests were carried out for a period of 6 months. At the end of the investigation it was possible to demonstrate the effectiveness of Cryopreservation, since the seeds subjected to the treatment with liquid nitrogen maintained their viability with 83% germination power, while the seeds subjected to the traditional freezing technique were losing their viability obtaining 43% germination power.